LEXICAL ERRORS AND FALSE COGNATES IN CROATIAN EFL LEARNERS: CHALLENGES AND PEDAGOGICAL IMPLICATIONS - Miličić, Ivona; Matanović, Mia (English Review: Journal of English Education, 2025)
Lexical errors and false cognates pose significant challenges for Croatian learners of English as a Foreign Language (EFL), often leading to miscommunication and reduced linguistic accuracy. This study examines common lexical errors arising from direct translation, semantic misinterpretation, and interference from Croatian, with a particular focus on false cognates—words that appear similar in both languages but have different meanings. Using a mixed-method approach, data were collected through error analysis of student writing samples and teacher observations from Croatian EFL classrooms. The findings reveal that Croatian learners frequently misapply English vocabulary due to phonetic and semantic similarities with Croatian words, leading to errors that hinder fluency and comprehension. Additionally, the study explores how limited exposure to authentic English input and insufficient focus on lexical differentiation in curricula contribute to these errors. Pedagogical strategies such as contrastive analysis, explicit vocabulary instruction, and corpus-based learning are recommended to mitigate these issues. This research underscores the need for targeted interventions in Croatian EFL teaching to enhance lexical competence and foster more accurate language use among learners.